Aracnoiditis cerebral y espinal en un paciente con neurocisticercosis: reporte de caso - Pablo A. Botero-C (Infectio)
Introduction: Arachnoiditis is a chronic inflammatory process of the arachnoid layer and subarachnoid space, and many possible etiologies can cause it, including infectious diseases. Case report: A patient with brain and spinal arachnoiditis was diagnosed and managed on the basis of clinical suspicion as tuberculous meningitis, but when he finished corticosteroids he presented neurological worsening, and after serum western blot immunoassay of T. solium positive, a possible racemose neurocysticer-cosis was diagnosed and treated. Conclusion: Doctors should consider the importance of nontuberculous etiologies in countries where both neurocysticercosis and tuberculosis are endemic, espe-cially when exist arachnoiditis with cranial basal involvement.